Pathology of the gastrointestinal tract in overweight and obese children - Menshchikova, V. Е.; Kartseva, Т. V.; Eliseeva, D. V.; Ryabichenko, Т. I.; Obukhova, О. О.; Zalavina, S. V. (Sibirskiĭ nauchnyĭ medit︠s︡inskiĭ zhurnal, 2024)
Obesity and diseases of the gastrointestinal tract are widespread among the children and have common developmental mechanisms. The article provides a literature review on the relationships between certain pathological conditions of the digestive system (gastroesophageal reflux disease, gastritis, functional intestinal disorders, Crohn’s disease, diverticular disease) in children with overweight and obesity. Excess body weight and obesity can become risk factors for the development of gastrointestinal pathology. The data available in modern literature on changes in the composition of the intestinal and stomach microbiocenosis with increasing body weight are summarized (changes in enterotype, increase in the Firmicutеs/Bacteroides ratio, increase in the number of bacteria Methanobrevibacter, Escherichia coli, Lactobacillus rhamnosus, Lactobacillus delbrueckii and Lactobacillus reuteri ). The strains of bacteria that contribute to the anorexigenic effect are considered: Lactobacillus gasseri , some strains of Bifidobacterium , Saccharomyce s, Streptococcus and Enterococcus . The pathogenetic aspects of obesity and overweight caused by microbiota are presented: activation of lipid synthesis, breakdown of polysaccharides, absorption of mono- and disaccharides, development of metabolic endotoxemia, etc. Features of the functioning of the autonomic nervous system in obesity in children are presented, indicating the predominance of the hypersympathicotonic variant of autonomic reactivity.